Pengaruh Etika Profesi, Kompetensi dan Integritas Auditor Terhadap Kualitas Audit (Studi Empiris Pada Kantor Akuntan Publik di Kota Medan) - Angelica Medistra Megaviesta Fau; Panondang Siagian; Wilsa Road Betterment Sitepu (Politeknik Ganesha Medan, 2021)
The auditor is a party that has an important role in auditing financial statements which is used as a benchmark in decision making in an entity. An auditor should be able to uphold his professional ethics and have the competence to be able to do his job. Not only that, because it is in the thick of the interests of various parties, the auditor must have the integrity to be able to state the findings by the actual circumstances. This study aims to determine how Professional Ethics, Competence, and Auditor Integrity affect Audit Quality. The data in this research were obtained through distributing questionnaires and using a sample of 94 auditors who work at 22 public accounting firms in Medan. The research was carried out by obtaining data through a survey using a Likert scale as a benchmark and processing through SPSS. The sample is determined by the probability sampling method and the research model uses the T and F test or also known as multiple liner analysis. Besides, this study also uses classic assumption tests, multicollinearity, and heteroscedasticity to see how competence, integrity, and professional ethics affect audit quality. This study obtained results indicating that, simultaneously and partially, integrity and professional ethics affect audit quality. Meanwhile, competence does not affect significantly and partially but affects simultaneously